Study of Morphological Types of Anemia in Antenatal Patients at a Tertiary Care Hospital - Krishnan, Geethu; Shah, Pragnesh H. (Annals of Pathology and Laboratory Medicine, 2025)
Background: Anemia, defined as a decrease in hemoglobin concentration below normal levels adjusted for age, sex, and environment, reduces the blood's oxygen-carrying capacity. It is a major public health issue, especially in developing countries. In India, 52.1% of pregnant women in rural areas and 45.7% of those in urban areas suffer from anemia. This study aimed to classify the morphological types and severity of anemia in antenatal patients and correlate them with pregnancy trimesters. Methods: At Sir T Hospital in Bhavnagar, a cross-sectional study was carried out between January 1 and December 31, 2022. Automated hematology analyzers were used to examine 226 pregnant women's blood samples. The formula n=Z²pq/d² was used to get the sample size. Results: Microcytic hypochromic anemia was the most common type (36%), followed by dimorphic (23%), macrocytic (21%), and normocytic normochromic (20%). Most common was moderate anemia (55%), which was followed by severe (28%) and mild (17%) anemia. Anemia cases were evenly spread across trimesters, with slightly higher rates in the first and second. Most patients were aged 20 to <30 years. Conclusion: Anemia in pregnancy remains highly prevalent, with 83% of cases observed in this study, particularly among women aged 18-25. It poses serious risks to maternal and fetal health, including long-term consequences for the child's development and future health.